National Coaching Institutes
Vorstellung der Trainerausbildungsinstitute Kanadas: National Coaching Institutes The National Coaching Institutes (NCI), located in Montréal, Winnipeg , Victoria and Calgary, are Canada's most comprehensive learning experience for high performance coaches. They offers a unique opportunity to learn from some of Canada's most experienced coaches and most sought-after sport science experts. The program is geared specifically to each candidate's sport, yet provides an opportunity to share common coaching elements and solutions with other students in the program. Those seeking admission to the NCI require 3M NCCP Level 3 certification, endorsement from their National Sport Federations as a 3M NCCP Level 4 candidate, and a minimum of three years' experience coaching athletes in a year-round training program. The tuition fee for the NCI is $2,000. Coaches accepted into the program may be eligible for a scholarship valued from $2,000 to $8,000.